Připravenost studenta učitelství: sebehodnocení v jádrových dovednostech výuky - Kratochvílová, Jana (Masaryk University Press, 2022)
Title in English: Preparedness of Teacher Education Students: Self-assessment in Core Teaching Skills The presented instrument is an contribution to the issue of teacher education evaluation for faculties preparing teachers across disciplines. The purpose of the instrument is to provide teacher educators an simple summative tool to allow them to measure and compare the current state and development of the level of the professional preparation of students and graduates in field of teaching.